Observing the release of twist by magnetic reconnection in a solar filament eruption - Zhike Xue (Nature Portfolio, 2016)
Magnetic reconnection is a fundamental process giving rise to topology change and energy release in plasmas, of particular relevance for the Sun. Here the authors report the observation of fast reconnection in a solar filament eruption, which occurs between a set of ambient fibrils and the filament itself.